Frontiers in Software Engineering Education c - Bruel, Jean-Michel.; Capozucca, Alfredo; Mazzara, Manuel; Meyer, Bertrand; Naumchev, Alexandr; Sadovykh, Andrey; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2020)
This book constitutes invited papers from the First International Workshop on Frontiers in Software Engineering Education, FISEE 2019, which took place during November 11-13, 2019, at the Château de Villebrumier, France. The 25 papers included in this volume were considerably enhanced after the conference and during two different peer-review phases. The contributions cover a wide range of problems in teaching software engineering and are organized in the following sections: Course experience; lessons learnt; curriculum and course design; competitions and workshops; empirical studies, tools and automation; globalization of education; and learning by doing. The final part "TOOLS Workshop: Artificial and Natural Tools (ANT)" contains submissions presented at a different, but related, workshop run at Innopolis University (Russia) in the context of the TOOLS 2019 conference. FISEE 2019 is part of a series of scientific events held at the new LASER center in Villebrumier near Montauban and Toulouse, France.
COURSE EXPERIENCE -- Teaching Formal Methods: An Experience Report -- A review of the structure of a course on Advanced Statistics for Data Scientists -- Reflection on Teaching Formal Approaches for Software Development in Higher Education -- Experience of mixed learning strategies in teaching Lean Software Development to third year undergraduate students -- Teaching Theoretical Computer Science at Innopolis University -- LESSONS LEARNT -- Teaching Software Testing to Industrial Practitioners using Distance and Web-Based Learning -- Towards code review guideline in a Classroom -- IT education in St. Petersburg State University -- Ten Unsafe Assumptions When Teaching Topics in Software Engineering -- CURRICULUM AND COURSE DESIGN.-Analysing the SWECOM standard for designing a DevOps education programme -- Teaching Logic, from a Conceptual Viewpoint -- On the Design of a New Software Engineering Curriculum in Computer Engineering -- Collaborative Modelling and Co-simulation in Engineering and Computing Curricula -- COMPETITIONS AND WORKSHOPS -- Designing Interactive Workshops for Software Engineering Educators -- Hackathons as a Part of Software Engineering Education: CASE in Tools Example -- Teaching E cient Recursive Programming and Recursion Elimination using Olympiads and Contests Problems -- EMPIRICAL STUDIES -- Experience in monitoring EEG signals during summer student internships -- A Study of Cooperative Thinking -- TOOLS AND AUTOMATION -- Analysis of Development Tool Usage in Software Engineering Classes -- Applying test-driven development for improved feedback and automation of grading in academic courses on software development -- GLOBALIZATION OF EDUCATION -- Internationalization Strategy of Innopolis University -- Finding the Right Understanding: Twenty-First Century University, Globalization and Internationalization -- TOOLS Workshop: ARTIFICIAL AND NATURAL TOOLS (ANT) -- Automated Cross-Language Integration Based on Formal Model of Components -- Scalable Thread-Modular Approach for Data Race Detection -- On the development of the compiler from C to the processor with FPGA accelerator.
Keywords: Software engineering; Computer programming; Education Data processing; Computer logic; Database management; Software Engineering/Programming and Operating Systems; Programming Techniques; Computers and Education; Logics and Meanings of Programs; Database Management